Platelet P2Y12 Inhibitors Reduce Systemic Inflammation and Its Prothrombotic Effects in an Experimental Human Model. Issue 12 (December 2015) - Thomas, Mark R.; Outteridge, Samuel N.; Ajjan, Ramzi A.; Phoenix, Fladia; Sangha, Gurpreet K.; Faulkner, Rachael E.; Ecob, Rosemary; Judge, Heather M.; Khan, Haroon; West, Laura E.; Dockrell, David H.; Sabroe, Ian; et al.
Abstract : Objective—: Clinical studies suggest that platelet P2Y12 inhibitors reduce mortality from sepsis, although the underlying mechanisms have not been clearly defined in vivo. We hypothesized that P2Y12 inhibitors may improve survival from sepsis by suppressing systemic inflammation and its prothrombotic effects. We therefore determined whether clopidogrel and the novel, more potent P2Y12 inhibitor, ticagrelor, modify these responses in an experimental human model. Approach and Results—: We randomized 30 healthy volunteers to ticagrelor (n=10), clopidogrel (n=10), or no antiplatelet medication (controls; n=10). We examined the effect of P2Y12 inhibition on systemic inflammation, which was induced by intravenous injection of Escherichia coli endotoxin. Both P2Y12 inhibitors significantly reduced platelet–monocyte aggregate formation and peak levels of major proinflammatory cytokines, including tumor necrosis factor α, interleukin-6, and chemokine (C–C motif) ligand 2. In contrast to clopidogrel, ticagrelor also significantly reduced peak levels of IL-8 and growth colony-stimulating factor and increased peak levels of the anti-inflammatory cytokine IL-10. In addition, ticagrelor altered leukocyte trafficking. Both P2Y12 inhibitors suppressed D-dimer generation and scanning electron microscopy revealed that ticagrelor also suppressed prothrombotic changes in fibrin clot ultrastructure. Conclusions—: Potent inhibition of multiple inflammatory and prothrombotic mechanisms by P2Y12 inhibitors demonstrates critical importance of platelets as central orchestrators of systemic inflammation induced by bacterial endotoxin. This provides novel mechanistic insight into the lower mortality associated with P2Y12 inhibitors in patients with sepsis in clinical studies. Abstract : Supplemental Digital Content is available in the text.